Determinan Korupsi dengan Fraud Hexagon dalam Perspektif Dinas Kesehatan Jawa Barat - Dinata, Rury Octari; Asih, Dewi Kartika (Politeknik Ganesha Medan, 2024)
The rise of corruption cases that occur in city/district government, increasing cases of Corruption in the health sector every year, the West Java region, which included in the top three regions with the most corruption cases, also Corruption which ASN/PNS mainly carries out can reduce trust society to the government and the decline in government performance. This study aims to analyze the influence of Pressure, Collusion, Capability, Opportunity, Rationalization, and Ego on Corruption based on the perceptions of Health Service employees. The population of this study is employees at one of the West Java Regional Health Offices, totaling 146 people. Sampling using convenience sampling method with a total sample of 76 respondents. This research uses quantitative research and primary data by distributing questionnaires and testing the hypothesis using multiple linear regression analysis using IBM SPSS Statistics 26 software. This study showed that Rationalization has a positive and significant effect on Corruption, and Ego has a negative and significant effect. While the other variables, namely Pressure, Collusion, Capability, and Opportunity, do not affect Corruption. This research has several limitations, including the lack of comparative references because Fraud Hexagon is still relatively new, and the distribution of questionnaires was direct, so it took a long time. The distribution is only in one government agency, so the sample used and the research area are still limited.